Frequency-comb-referenced quantitative phase imaging for high-sensitivity, high-speed, spectroscopic phase measurement - Boonruangkan, Jeeranan (Nanyang Technological University, 2020)
QPI (Quantitative Phase Imaging) is an innovative optical imaging technique which has been widely used for study biological tissues and cells. In QPI, the coherence of the optical field is the prerequisite for high-resolution imaging. However, the use of coherence inevitably accompanies phase ambiguity and coherent artifacts (i.e., speckles) which will degrade phase resolution and hinder successful phase reconstruction. Here, this research proposes a rotational optical diffuser as a compact, vibration-free, and effective method to suppress the speckle of high-coherence continuous-wave laser (background noise is reduced by 1.36 dB). However, a single continuous-wave laser source cannot satisfy phase-coherent multiple wavelengths so our first method can offer the advantages to some potential applications. Therefore, this research further proposes a second speckle-suppression method to obtain highly sensitive phase images and this method can provide multiple capabilities across a broad range of applications. The use of frequency comb as a light source in QPI, which is named here as the frequency-comb-referenced quantitative phase imaging (FCR-QPI), is proposed for providing coherence tunability for speckle-suppressed interferogram (Lc: 8.1 to 56.3 m, V: 0.63 to 0.98), phase-coherent multiple wavelengths for measuring cellular degradation, and higher phase stability (Allan deviation: 2.39×10-3 at 10-s averaging time) at a higher speed up to 16.9 kHz. In addition, FCR-QPI was demonstrated as a new technique for study heart rate and blood flow development in an embryonic zebrafish. Therefore, FCR-QPI could be recognized as a remarkable technique for driving the future of biological and biomedical imaging.